The legitimacy of generation in the islamic jurisprudence and the iranian legal - Babookani, Ehsan Aliakbari; Bibak, Bahar (Opción, 2019)
In the present paper, we dealt with the importance of adhering to the preservation of generational purity from the perspective of the Qur’anic verses, the traditions of the Infallibles (PBUT; Peace Be Upon Them), and decrees independently derived from reason via comparative qualitative research methods. As a result, it seems that in any legal systems, such prohibitions are considered rational and in accordance with the interests of society. In conclusion, all decrees on legitimate children are applicable to illegitimate children, unless what is excluded for a reason.